Order, please! Explicit sequence learning in hybrid search in younger and older age. - Wiegand, Iris; Westenberg, Erica; Wolfe, Jeremy M. (Memory & Cognition, 2021)
Sequence learning effects in simple perceptual and motor tasks are largely unaffected by normal aging. However, less is known about sequence learning in more complex cognitive tasks that involve attention and memory processes and how this changes with age. In this study, we examined whether incidental and intentional sequence learning would facilitate hybrid visual and memory search in younger and older adults. Observers performed a hybrid search task, in which they memorized four or 16 target objects and searched for any of those target objects in displays with four or 16 objects. The memorized targets appeared either in a repeating sequential order or in random order. In the first experiment, observers were not told about the sequence before the experiment. Only a subset of younger adults and none of the older adults incidentally learned the sequence. The "learners" acquired explicit knowledge about the sequence and searched faster in the sequence compared to random condition. In the second experiment, observers were told about the sequence before the search task. Both younger and older adults searched faster in sequence blocks than random blocks. Older adults, however, showed this sequence-learning effect only in blocks with smaller target sets. Our findings indicate that explicit sequence knowledge can facilitate hybrid search, as it allows observers to predict the next target and restrict their visual and memory search. In older age, the sequence-learning effect is constrained by load, presumably due to age-related decline in executive functions.